(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article highlights current issues in presenting works of applied art in museums through modern technologies. It analyzes the importance of multimedia tools, digital technologies, virtual and augmented reality, interactive exhibitions, and 3D modeling methods in museum work. The role of innovative technologies in promoting national examples of applied art and conveying them to the younger generation is also explained on a scholarly basis.The article also discusses how many museums, drawing on the experience of museums in a number of developed countries, are developing new approaches to preserving and displaying works of applied art through the use of modern technologies. It further examines the practical work being carried out in this area at the Ichan-Qal’a State Museum-Reserve. Information is provided on the importance of presenting tangible cultural heritage through innovative methods in order to widely promote the history, culture, and art of our country.